INCREASING WAREHOUSE THROUGHPUT THROUGH THE DEVELOPMENT OF A DYNAMIC CLASS-BASED STORAGE ASSIGNMENT ALGORITHM - McInerney, Sara Elizabeth; Yadavalli, Sarma (The South African Journal of Industrial Engineering, 2022)
This study investigates the problems faced by an agricultural wholesaler arising from an inefficient random storage assignment policy. Research was conducted on warehouse operations and storage policies. The ABC classification technique was used to create a class-based storage assignment policy. This policy was then input into an algorithm that packs products according to how frequently they are ordered. The aim of the algorithm is to store fast-moving products closest to the shipping area. If this is done, the order picking times would decrease by an average of 3 hours 20 mins per day. This would increase the warehouse’s throughput and profitability.